Large‐Scale Smart Carpet for Self‐Powered Fall Detection. Issue 2 (14th January 2020) - Yu, Aifang; Wang, Wei; Li, Zebin; Liu, Xia; Zhang, Yang; Zhai, Junyi
Abstract: Fabric has long‐term and the closest relationship to humans and is one of the measures of human progress and civilization. Functional fabrics are vigorously developed over the past few decades due to the explosive increase in portable electronic products. Fall detection is becoming increasingly important with the recent rapid aging of the population. Here, a pressure‐sensitive and large‐scale carpet for self‐powered fall detection, which is based on the textile‐triboelectric nanogenerators (t‐TENGs) arrays inlaid in common textile, is proposed. Core–shell yarns with conductive fibers as the core and common clothing fibers as the shell fabricated by a commercially available weaving method are used to constructed the smart t‐TENGs. The fabricated smart carpet exhibits desirable features including high sensitivity, fast response time, scalable production, comfortability, washability, and compatibility with existing home decoration. Furthermore, apart from highly integrated data acquisition and processing, arrangement of t‐TENGs cells and trigger algorithm are deliberately designed to effectively and simply realize real‐time and self‐powered falling behavior monitoring. Possessing these unique merits, the proposed system demonstrates great potential in more humanized medical healthcare systems and can be applied to innumerable families. Abstract : A large‐scale smart carpet is successfully displayed for self‐powered fall detection, which is based on the textile‐triboelectric nanogenerators arrays inlaid in common textile. The fabricated smart carpet exhibits desirable features including high sensitivity, fast response time, scalable production, comfortability, washability, and compatibility with existing home decoration.